Some properties of polynomial maps in terms of newton polyhedrons - Phạm, Phú Phát (Trường Đại học Đà Lạt, 2024)
The main purposes of this thesis are to study some properties of polynomial maps including monodromies and the compactness of algebraic sets defined by a class of polynomials satisfying non-degeneracy condition in terms of Newton polyhedron with some tools of Singularity theory and Semi-Algebraic Geometry.